2018
DOI: 10.1557/jmr.2018.350
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic consideration of earth-abundant chalcogenide materials for photovoltaics: Kesterite and beyond

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…72 It appears more than likely that similar phenomena should be observed in other vacancy-containing compounds with complex unit cells, for instance K 2.5 Bi 8.5 Se 14 , 73 K 2 Bi 8 Se 13 , 74 and (Yb,Eu,Ca,Sr) 9 (Mn,Zn,Cd) 4+x (Sb,Bi) 9 . 75,76 Quite a few investigations of order−disorder transitions for systems with mixed occupancies have also been reported, which include Cu 2 (Zn,Cd,Hg) (Si,Ge,Sn)Te 4 77 and II−IV−− V 2 78 semiconductors, Cu 2 SnS 3 , 79 Cu 2 ZnSn(S,Se) 4 , 80 LAST alloys, 81 and perovskite oxynitrides. 82 Based on our study, we expect that the same holds true for other alloys, which include "unconventional" superconductors, 83 nitride semiconductors, 84 inverse 85 and full 86 Heuslers, chalcogenides, 87−89 pavonites, 90,91 pnictides, 92−94 phosphides, 95 oxides, 96,97 and Chevrel 98,99 and Zintl 100−102 phases.…”
Section: ■ Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…72 It appears more than likely that similar phenomena should be observed in other vacancy-containing compounds with complex unit cells, for instance K 2.5 Bi 8.5 Se 14 , 73 K 2 Bi 8 Se 13 , 74 and (Yb,Eu,Ca,Sr) 9 (Mn,Zn,Cd) 4+x (Sb,Bi) 9 . 75,76 Quite a few investigations of order−disorder transitions for systems with mixed occupancies have also been reported, which include Cu 2 (Zn,Cd,Hg) (Si,Ge,Sn)Te 4 77 and II−IV−− V 2 78 semiconductors, Cu 2 SnS 3 , 79 Cu 2 ZnSn(S,Se) 4 , 80 LAST alloys, 81 and perovskite oxynitrides. 82 Based on our study, we expect that the same holds true for other alloys, which include "unconventional" superconductors, 83 nitride semiconductors, 84 inverse 85 and full 86 Heuslers, chalcogenides, 87−89 pavonites, 90,91 pnictides, 92−94 phosphides, 95 oxides, 96,97 and Chevrel 98,99 and Zintl 100−102 phases.…”
Section: ■ Discussionmentioning
confidence: 69%
“…In fact, there exist several studies that have shown the importance of transformations between states with ordered and disordered vacancies or at least considered their existence in functional materials such as Li x CoO 2 , Zn 5 Sb 4 In 2−δ , zinc antimonides, , ZnAl 2 O 4 , Mg 3 (Bi,Sb) 2 , AgCrSe 2 , Ag 8 SiSe 6 , (Tm,Y) (Ag,Cu)­Te 2 , Cu 2– x Se, , Cu 7 PSe 6 , Cu 7 PSe 6– x S x , GeTe, half-Heuslers, , and partially filled skutterudites . It appears more than likely that similar phenomena should be observed in other vacancy-containing compounds with complex unit cells, for instance K 2.5 Bi 8.5 Se 14 , K 2 Bi 8 Se 13 , and (Yb,Eu,Ca,Sr) 9 (Mn,Zn,Cd) 4+ x (Sb,Bi) 9 . , Quite a few investigations of order–disorder transitions for systems with mixed occupancies have also been reported, which include Cu 2 (Zn,Cd,Hg) (Si,Ge,Sn)­Te 4 and II–IV––V 2 semiconductors, Cu 2 SnS 3 , Cu 2 ZnSn­(S,Se) 4 , LAST alloys, and perovskite oxynitrides . Based on our study, we expect that the same holds true for other alloys, which include “unconventional” superconductors, nitride semiconductors, inverse and full Heuslers, chalcogenides, pavonites, , pnictides, phosphides, oxides, , and Chevrel , and Zintl phases.…”
Section: Discussionmentioning
confidence: 99%
“…Solar energy, as one of the renewable and sustainable resources, has a minimum impact on environment and has been extensively explored and utilized. It can generate green powder through devices such as photovoltaic devices, supercapacitors, and photoelectrochemical (PEC) devices. Among these devices, PEC cells possess an environmentally friendly route toward converting solar energy into chemical energy. So far, CdTe, Cu­(In,Ga)­(S,Se) 2 , and Cu 2 ZnSn­(S,Se) 4 (CZTS) have drawn much attention as prospective photocathodes for PEC application because of their higher absorption coefficient, tunable band gap between 1.0 and 2.4 eV, and high carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy, as one of the renewable and sustainable resources, has a minimum impact on environment and has been extensively explored and utilized. It can generate green powder through devices such as photovoltaic devices, 1 supercapacitors, and photoelectrochemical (PEC) devices. 2−5 Among these devices, PEC cells possess an environmentally friendly route toward converting solar energy into chemical energy.…”
Section: Introductionmentioning
confidence: 99%